PREDICTORS OF THE USE OF GASTROPROTECTIVE AGENTS IN PATIENTS USING NSAID IN YOGYAKARTA INDONESIA - Ady Bagus Indrianto; Jarir At Thobari; Agung Endro Nugroho (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Non Steroid Anti-Inflammatory (NSAID) is one type of AntiInflammatory drug that is used to treat pain in patients of osteoarthritis (OA) and rheumatoid arthritis (RA). The use of NSAIDs can cause gastrointestinal side effects. To prevent the side effects, NSAIDs are prescribed in combination with gastroprotective agent (GPA). The aim of the study is to determine the factors considered in the GPA prescription by the doctors in patients who have risk factors for gastric disorder due to NSAIDs use. This study was performed using a cross-sectional observational design. The data were collected retrospectively during a period of January to December 2010. The subjects were OA and RA patients considering the inclusion and exclusion criteria. The data included patient characteristics (gender, age, occupation, payment method, the primary diagnosis), prescription of NSAID, prescription of GPA, history of gastrointestinal disease, NSAID prescription with corticosteroids, prescription with antiplatelet. The data were processed descriptively and quantitatively, and analyzed statistically using chi-square and log. regression with 95% Confidence Interval. The results showed that there were correlation between some predictor factors with prescription of gastroprotective agent. These factors were women patient, patient age of ≥ 65 years, oxicam prescribing, diclofenac sodium prescribing, prescribing >1 type of NSAIDs, prescription of NSAID concomitant with corticosteroids, prescription of NSAID concomitant with antiplatelet, patients with history of gastrointestinal, prescribing NSAIDs with duration of ≥ 3 months. Patient with a history of gastrointestinal disease was the most predictor influential factor, with OR (odds ratio) of 3.6 (95% CI: 2.79 - 4.66). Predictor factor of patients with a history of dyspepsia possessed the highest OR OR=4,29 (CI 95%: 3.23–5.7). It means that patients with a history of dyspepsia prescribed NSAIDs would have greater risk of 4.29 times to get GPA prescription than patients without a history of dyspepsia. Prescribing NSAIDs > 1 DDD (defined daily dose) had p value of 0.777, which means there was no relationship between GPA prescription with NSAIDs > 1 DDD prescription.Key words: Gastroprotective Agent, Non-steroid anti-inflammatory, Osteoarthritis, Rheumatoid Arthritis